Toll Like Receptors as Sensors of the Tumor Microbial Dysbiosis: Implications in Cancer Progression - Le Noci, Valentino; Bernardo, Giancarla; Bianchi, Francesca; Tagliabue, Elda; Sommariva, Michele; Sfondrini, Lucia (Frontiers in Cell and Developmental Biology, 2021)
Microbiota is a complex ecosystem of active microorganisms resident in the body of mammals. Although the majority of these microorganisms resides at the distal gastrointestinal tract, high-throughput DNA sequencing technology have made possible to understand that several other tissues of the human body host their own microbiota, even those once considered sterile, such as lung tissue. These bacterial communities have important functions in maintaining a healthy body state and the host immune system has evolved multiple mechanisms by which maintaining a symbiotic relationship with the microbiota. The maintenance of this dialogue allows the induction of protective responses to pathogens and regulatory pathways that sustain the tolerance to commensal microbes. Toll-like receptors (TLRs) play a central role in sensing the microbiota, maintaining the tolerance or triggering an immune response through the direct recognition of ligands derived from commensal microbiota or pathogen microbes. Lately, it has been highlighted that the resident microbiota can impact on cancer initiation, progression and response to therapies and that specific changes, in term of number and distribution of taxa, are associated with the presence of cancer in various tissues. However, the knowledge of functional activity and the meaning of microbiome changes remain limited. In this review, we summarized the current findings on the role of TLRs as sensors of the microbiota and highlighted their modulation as mirror of tumor associated changes of the commensal microbiota. It appears that dysbiosis of commensals in cancer tissues is sensed by TLRs expressed on cancer cells and on immune infiltrating cells, whose activations result in a direct proliferative stimulation of tumor, or in a chronic inflammatory condition that can enforce the tumor immunosuppressive microenvironment. Thus, these observations suggest that commensal “onco-microbes” might be able to break the tolerance of TLRs and become complicit of cancer by sustaining its growth.